Answer:The obvious difference between substitution and elimination reactions is that substitution reactions replace one substituent with another while elimination reactions simply remove the substituent. ... The major difference between the groups is the number of steps the reaction takes place over.
Step-by-step explanation:
Answer:
The smallest zero is -3.
Step-by-step explanation:
<h2>
<u>QUADRATIC EQUATION</u></h2>
<h2>
![\mathbb{ANSWER:}](https://tex.z-dn.net/?f=%20%5Cmathbb%7BANSWER%3A%7D)
</h2>
— — — — — — — — — —
<h3>
Step-by-step explanation:</h3>
<u>How can </u><u>we</u><u> factor 5x^2 + 26x - 24 = 0 using the completing the square </u><u>method?</u>
Let's solve your equation step-by-step.
![\bold{Given \: Equation: \color{brown} 5x²+26x-24=0}](https://tex.z-dn.net/?f=%20%5Cbold%7BGiven%20%5C%3A%20%20Equation%3A%20%5Ccolor%7Bbrown%7D%205x%C2%B2%2B26x-24%3D0%7D)
First, add 24 to both sides.
Since the coefficient of 5x² is 5, divide both sides by 5.
The coefficient of 26/5x is 26/5. So, let b=26/5.
Then we need to add (b/2)²=169/25 to both sides to complete the square.
Add 169/25 to both sides.
Factor the left side.
Take square root.
Then, add (-13)/5 to both sides.
_______________❖_______________
Answer:
f(g(x)) = 2x +(-5)
Step-by-step explanation:
Put the argument value into the function and simplify the result.
f(g(x)) = f(x -3) = 2(x- 3) +1 = 2x -6 +1
f(g(x)) = 2x +(-5)
Step-by-step explanation:
Let set up the two column proof
Statements. Reasons
1. m 1+ m∠5 = 180° and m∠1 + m∠4=180° Given
2. 2. m∠1 + m∠5 = m∠1 + m∠4. Substitution
3.m∠5 = m∠4. Subtraction Property of Equal
4.is Parallel to Given. 4.If alternate interior angles equal, then lines are ||.